2003
DOI: 10.1021/jf0262458
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Compounds from the Leaves of Peucedanum japonicum Thunb

Abstract: Seventeen compounds were isolated from the n-butanol soluble fraction of the leaves of Peucedanum japonicum Thunb. On the basis of MS and various NMR spectroscopic techniques, the structures of the isolated compounds were determined as isoquercitrin (1), rutin (2), 3-O-caffeoylquinic acid (3), 4-O-caffeoylquinic acid (4), 5-O-caffeoylquinic acid (5), cnidioside A (6), praeroside II (7), praeroside III (8), apterin (9), esculin (10), (R)-peucedanol (11), (R)-peucedanol 7-O-beta-d-glucopyranoside (12), l-tryptop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 41 publications
2
53
0
Order By: Relevance
“…The chemical structures of those isolated compounds with purity higher than 90% were identified as praeroside III (1) [25], umbelliferone (2) [26], rutaretin (3) [27], (−)-cis-khellactone (4) [27], nodakenetin (5) [19,28], bergapten (6) [28,29], xanthotoxin (7) [29], Pd-Ib (8) [21], d-laserpitin (9) [20], nodakenetin tiglate (10) [30], praeruptorin A (11) [21], decursinol angelate (12) [28], corymbocoumarin (13) [31], qianhucoumarin J (14) [20], praeruptorin B (15) [21] and praeruptorin E (16) [21], by ESI-MS and 1 H, 13 C NMR data (Supporting Information), which were consistent with the authentic samples or literature data.…”
Section: Identification Of Isolated Compoundsmentioning
confidence: 99%
“…The chemical structures of those isolated compounds with purity higher than 90% were identified as praeroside III (1) [25], umbelliferone (2) [26], rutaretin (3) [27], (−)-cis-khellactone (4) [27], nodakenetin (5) [19,28], bergapten (6) [28,29], xanthotoxin (7) [29], Pd-Ib (8) [21], d-laserpitin (9) [20], nodakenetin tiglate (10) [30], praeruptorin A (11) [21], decursinol angelate (12) [28], corymbocoumarin (13) [31], qianhucoumarin J (14) [20], praeruptorin B (15) [21] and praeruptorin E (16) [21], by ESI-MS and 1 H, 13 C NMR data (Supporting Information), which were consistent with the authentic samples or literature data.…”
Section: Identification Of Isolated Compoundsmentioning
confidence: 99%
“…It has been reported that coumarins (Chen et al 1996;Ikeshiro et al 1994Ikeshiro et al , 1993Ikeshiro et al , 1992Duh et al 1992), chromones, polyacetylenes (Lee et al 2000), sugar alcohols (Lee et al 2004), and steroid glycosides (Shin et al 1992) were isolated from the roots of P. japonicum. Phytochemical studies proved that P. japonicum leaves possess coumarins (Jang et al 2008;Hisamoto et al 2003), flavonoids, phenylpropanoid glycosides (Hisamoto et al 2004), phenol derivatives, C13 norisoprenoid glycosides, nucleosides, nucleobases, amino acids, and benzofuran glycosides. Based on the literature survey, it was revealed that the angular 2 dihydropyranocoumarins are major constituents of P. japonicum roots.…”
Section: Peucedanum Japonicum Thunberg Is Widely Distributed In Southmentioning
confidence: 99%
“…(PJ), which belongs to the Umbelliferae family, has been widely used as traditional medicine and supplement used to produce food. In recent decades, studies have indicated that PJ may have antioxidant, anti-obesity and anti-spasmolytic properties (1)(2)(3). Notably, it was demonstrated that compounds isolated from PJ exert antagonistic effects on smooth muscle contraction by altering free cytoplasmic Ca 2+ ( [Ca 2+ ] i ) mobilization (3).…”
Section: Introductionmentioning
confidence: 99%